Sustainable groundwater management in India needs a water-energy-food nexus approach - Mukherji, Aditi (Wiley, 2022)
Groundwater depletion in India is a result of water, energy, and food policies that have given rise to a nexus where growth in agriculture has been supported by unsustainable trends in water and energy use. This nexus emanates from India’s policy of providing affordable calories to its large population. This requires that input prices are kept low, leading to perverse incentives that encourage groundwater overexploitation. The paper argues that solutions to India’s groundwater problems need to be embedded within the current context of its water-energy-food nexus. Examples are provided of changes underway in some water-energy-food policies that may halt further groundwater depletion.